Kerstersia gyiorum Isolated from a Bronchoalveolar Lavage in a Patient with a Chronic Tracheostomy - Meredith Deutscher; Jennifer Severing; Joan-Miquel Balada-Llasat (Case Reports in Infectious Diseases)
The use of the matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) generates rapid microbial identification. We are presenting a case of a 63-year-old woman with a medical history of chronic tracheostomy admitted for hypotension and fevers to illustrate the clinical implication of MALDI-TOF MS on bacterial identification. Kerstersia gyiorum was identified from the bronchoalveolar lavage isolate. Kerstersia gyiorum has been isolated from human sputum samples, and may be a previously unrecognized colonizer of the upper respiratory tract. Thus, patients with long-term tracheotomies or who are chronically aspirating may be at risk of lower respiratory infection with this organism. Increased use of MALDI-TOF MS in the clinical setting may increase reporting of this atypical isolate.